An Analytical Hierarchy Process-Based Development of a Setting and Infrastructure Assessment Tool for Green Campus: Refining the UI GreenMetric Framework - Mia Wimala (EMARA: Indonesian Journal of Architecture, 2025)
Open spaces serve aesthetic and ecological functions and are essential in the context of global sustainability, particularly in evaluating green buildings. The UI GreenMetric system incorporates open spaces in its Setting and Infrastructure criteria, but the assessment method requires further development to adapt to campus needs. This research seeks to establish assessment variables pertaining to open spaces, including their weights and scoring system. Comprehensive literature research of other similar instruments and relevant legislation was performed at an early stage. The Analytical Hierarchy Process is subsequently employed to assess the relative importance of the established variables. The findings highlight four categories for Setting and Infrastructure: Policies and Management of Landscape and Biodiversity (52%), Green Open Spaces (33%), Non-Green Open Spaces (12%), and Biodiversity (3%), along with subcategories and indicators for each category.